A Case Study of Feline Panleukopenia in Cats at The Educational Animal Hospital of Universitas Airlangga - Yusril Nur Mahendra; M. Gandul Atik Yuliani; Agus Widodo; Diyantoro Diyantoro; Miyayu Soneta Sofyan (Journal of Applied Veterinary Science And Technology, 2020)
Background: Feline panleukopenia is a viral disease caused by the family of Parvoviridae. Many species of pets, especially cats, that if they have been infected, compromised health and can lead to death. Purpose: To determine the infection pattern and treatment of feline panleukopenia in cats at the Educational Animal Hospital of Universitas Airlangga. Method: Ten patients were recorded as infected with parvovirus from a total of 1107 patients with various disease complaints. Daily records were taken regarding all clinical symptoms, physical examination, and treatment. Result: After four weeks, the obtained data were calculated. Thus, we collect data that show essential factors that can be used to determine the diagnose of feline panleukopenia in cats. Conclusion: Most parvovirus infections occurred in cats aged two to four years by showing abnormalities in temperature, breathing, and turgor. Clinical symptoms that appeared include vomiting, diarrhea, and high dehydration. Treatments were used to suppress the secondary effects of parvovirus infection and besides to eradicate the virus itself.